Genetic diversity of plasmodium falciparum isolated from Yemen based on the genes of merozoite surface proteins (msp-1 and msp-2) / Nazeh Mohammed Al-Abd Ali - Al-Abd Ali, Nazeh Mohammed (2011)
Malaria is a major health problem causing substantial morbidity and mortality with Plasmodium falciparum being the causative agent of the most severe and deadly form of malaria in humans. In Yemen Malaria is one of the most serious health problems. About 60% of the populations live in areas with malaria transmission. P. falciparum is the predominant species and accounts for more than 90% of malaria cases. Information on the nature and extent of genetic diversity within P. falciparum is essential for understanding the mechanism underlying the pathology of malaria, the acquisition of immunity, the spread of drug resistance and the condition of the transmission. This study was conducted in the high transmission area in Yemen (Taizz, Dhamar, and AL-Hudiydah) and was guided by the objective that were to establish molecular characterizations of field isolate P. falciparum in Yemen measured with polymorphic genetic markers of merozoite surface protein msp-1 and msp-2.